2021
DOI: 10.1155/2021/6614028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Intestinal Flora and Proteomics on Regulating Immune Function of Durio zibethinus Rind Polysaccharide

Abstract: In this study, cyclophosphamide was injected intraperitoneally to establish an immunosuppressive mouse model to study the immune regulating effects of Durio zibethinus Murr rind polysaccharide (DZMP) through proteomics and intestinal flora. The results showed that the thymus and spleen indexes of the high-dose DZMP (200 mg/kg) group were significantly increased, and the tissue structure of the spleen was improved compared with the model group ( P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…This is similar to previous studies that Wild morels polysaccharides and Lotus Seed Resistant Starch both augmented SCFAs levels in mice by increasing the content of SCFAsproducing Lachnospiraceae (56,62). Many polysaccharides have been confirmed to cause increased expression of Bacteroides (63)(64)(65)(66). Nevertheless, different sources of polysaccharides have different effects on the gut microbiota.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to previous studies that Wild morels polysaccharides and Lotus Seed Resistant Starch both augmented SCFAs levels in mice by increasing the content of SCFAsproducing Lachnospiraceae (56,62). Many polysaccharides have been confirmed to cause increased expression of Bacteroides (63)(64)(65)(66). Nevertheless, different sources of polysaccharides have different effects on the gut microbiota.…”
Section: Discussionsupporting
confidence: 91%
“…The spleens of mice in the BC, MC, and HD groups were taken, and after washing, the spleen tissues of each three mice were combined into one sample, and the obtained samples were subjected to proteomic assay (27).…”
Section: Proteomics Studiesmentioning
confidence: 99%
“…Moreover, researches on numerous studies on the edible fungi‐based research, associated characterization, and their findings are tabulated in Table 2. Jiang et al (2021) found through in vivo and in vitro experiments that edible fungus can significantly increase the binding of low‐affinity immunoglobulin γFc receptor III protein and protein kinase PKC‐α protein. This enhances the body's immunity; Hualei et al (2009) found that F. velutipes can increase the expression of mouse cellular immune factors such as IL‐2 and TNF‐α, enhance the activity of NK cells or T cells, thereby enhancing the body's immunity; Yuan et al (2020) studies have further shown that silver fungus can significantly promote the secretion of NO, IL‐1β, and TNF‐α by macrophages to enhance immunity.…”
Section: Immune Regulation Of Edible Fungusmentioning
confidence: 99%
“…A large number of studies have shown that edible fungi are closely related to humoral immunity, for example, edible fungus can significantly increase the binding of low‐affinity immunoglobulin γFc receptor III protein and protein kinase PKC‐α protein. In addition, edible fungi can increase the expression of mouse cell immune factors IL‐2 and TNF‐, enhance the activity of NK cells or T cells, thereby enhancing the body's immunity (Hualei et al, 2009; Jiang et al, 2021). Cellular immunity refers to the immune response mediated by T cells, macrophages, or NK cells, that is, cells are stimulated by antigens and produce cytotoxicity to achieve an effective means to eliminate intracellular parasitic microorganisms and reject allografts or tumor antigens.…”
Section: Introductionmentioning
confidence: 99%